These people have always been a republic : Indigenous electorate in the U.S.-Mexico borderlands, 1598-1912 - Crandall, Maurice (David J. Weber series in the new borderlands history., 2019)
"By focusing on this long history, Maurice Crandall demonstrates how Indigenous peoples absorbed, adapted, or eschewed colonially imposed forms of electoral politics and exercised political sovereignty based on local needs. In doing so, this study compares and contrasts not only Spanish, Mexican, and American conceptions of Indian citizenship, but also the differences among Indigenous groups that populated what became the states of Arizona and New Mexico. Crandall's work represents a significant contribution to the fields of Indigenous political rights and legal status in the American Southwest, as well as Indian-Hispano and Indian-Anglo relations in the U.S.-Mexico Borderlands"--